Optimalisasi Tri Pusat Pendidikan dalam Meningkatkan Literasi, Inklusivitas dan Karakter Anak di Desa Narawita Kabupaten Bandung - Ririn Nuraeni; Syayidah Nuriyah; Regi Ridwan Gunawan; Gian Ahdiningtias; Kurniawan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The real work activities (KKN) nusantara university in the village of narawita district of bandung, west Java province, aim to strengthen literacy, inclusive education and child character through family collaboration, school and community. Three major programs are started: bimbara (narawita study guide), inclusive educational training for teachers and kader posyandu, and the bullying seminar "sawala narawita". Flirtation methods include field observations, socializing, interactive training, and evaluations through pre-test and post-test. Program results show a significant increase in teacher and community understanding, with a 30% increase in post-test scores compared to pre-tests. Moreover, successful activities involve more than 100 participants from various elements of society such as village tools, peer-level pefiers at SDN 01 narawita, farmers, umkm people, villages and children. This activity proves that the policy-based approach to education is effective in creating inclusive and friendly learning ecosystems and has the potential to be replicated in the context of other villages. Keywords: Bullying, Child Character, KKN, Collaboration, Inclusive Education